How Do Different Mechanical Ventilation Modes (Volume-Controlled Vs Pressure-Controlled) Affect Patient Outcomes And Weaning Success In Intensive Care Unit Patients? : A Systematic Review - Ade Faisal; Melissa Theresia (International Medical Journal Corp. Ltd, 2025)
Introduction: Mechanical ventilation is a critical intervention in intensive care units (ICU), with volume-controlled ventilation (VCV) and pressure-controlled ventilation (PCV) being two primary modes. This study investigates how different mechanical ventilation modes, specifically volume-controlled versus pressure-controlled, impact patient outcomes and weaning success in adult ICU patients. Methods: A comprehensive search was conducted across over 126 million academic papers from the Semantic Scholar corpus, retrieving the 500 most relevant to the research question. Papers were screened based on predefined criteria, including adult ICU population, invasive mechanical ventilation, direct comparison of VCV and PCV, robust study designs (RCT, prospective cohort, systematic review/meta-analysis), and reporting of key outcomes such as mortality, ventilation duration, complications, or respiratory parameters. Data extraction from included studies was performed using a large language model to gather information on study design, blinding, patient characteristics, ventilation modes, and primary outcomes. Results: Analysis of the included studies revealed that pressure-controlled and hybrid ventilation modes generally improved respiratory mechanics, such as higher PaO2/FiO2 ratios, lower peak airway pressures, and higher dynamic compliance, compared to VCV. For example, one study reported a PaO2/FiO2 ratio of 176 with pressure-regulated volume control versus 146 with conventional volume control. While some studies showed shorter ventilation durations and more ventilator-free days with pressure-controlled or adaptive modes, others found no significant difference in weaning success. Overall, 11 studies reported significant differences favoring pressure-controlled ventilation or its variants in at least one measured domain (e.g., higher oxygenation, lower inflammation, shorter ventilation/ICU stay, less asynchrony, improved respiratory mechanics, fewer pulmonary complications). No study reported advantages for volume-controlled ventilation over pressure-controlled modes. Discussion: The physiological benefits observed with pressure-controlled modes, such as improved respiratory mechanics, do not consistently translate into improved clinical outcomes like reduced postoperative pulmonary complications, mortality, or duration of ventilation across all studies. This suggests that adherence to lung-protective strategies might be more crucial than the specific mode choice. Heterogeneity in patient populations, ventilation protocols, and outcome definitions, along with the prevalence of single-center studies and lack of blinding, are limitations affecting the generalizability and comparability of findings. Conclusion: Pressure-controlled and hybrid ventilation modes tend to offer superior or equivalent outcomes to volume-controlled modes, particularly in improving respiratory mechanics. While some studies indicate benefits in weaning success and reduced complications, these advantages are not universally observed across all clinical outcomes. The overall evidence quality is limited, highlighting the need for more robust, multicenter research. Keywords: Mechanical Ventilation, Volume-Controlled Ventilation, Pressure-Controlled Ventilation, Patient Outcomes, Weaning Success, Intensive Care Unit, Respiratory Mechanics.